Anesthetic Management of a Patient with Severe - Sadikova M.A. (Genius Journals, 2022)
Anesthetic management of the treatment of patients with scar contracture of the neck is associated with many problems. In this case, a 38-year-old woman with severe cicatricial contracture on her face, neck, front of her chest, and shoulders underwent flap surgery. We attempted a fiberoptic orotracheal intubation using the Glide Scope. Video laryngoscopy was performed after surgical removal of cicatricial contracture under local anesthesia. We report the successful treatment of a patient with severe burn contracture, achieved by the joint efforts of surgeons and anesthesiologists
Keywords: Acute fiberoptic intubation; burn contracture; videolaryngoscope